Dampak Motivasi Simbolis Kunjungan Wisatawan ke Destinasi Pariwisata Berbasis Ekowisata - Christianto, Jery; Adjie, Bergas Anggito; Larasita, Irma Dela; Furqan, Alhilal; Priscilia, Kiki; Sauky, M. Asfahani (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2023)
The popularity of ecotourism among foreign and domestic tourists is increasing in Indonesia. Uploading ecotourism content on social media can influence visitor decisions and give the uploader a feeling of satisfaction. Recognition through social media or symbolic motivation is one of the motivations for tourists to visit ecotourism. The number of tourists with symbolic motivation is increasing, in line with the increasing use of social media globally, which can have an impact on the development of ecotourism. This research identifies the factors of tourists with symbolic motivation wanting to visit two national parks (TNGL and TN Komodo) in Indonesia and the impacts arising from this phenomenon. The research is done with qualitative method, with data obtained through literature study and analysed descriptively. This study found that the factor for tourists with symbolic motivation who visited the two locations, namely because of the beautiful views and photo spots, different lifestyles offered by destinations, relaxation, the existence of exclusivity values in the facilities, and sensation seeking for attractions that have positive reviews in social media. This phenomenon has both positive and negative impacts on the environmental, economy, and socio-cultural aspects of these two national parks.